2009
DOI: 10.1007/s10457-009-9250-x
|View full text |Cite
|
Sign up to set email alerts
|

Cattle distribution and behavior in southern-pine silvopasture versus open-pasture

Abstract: Shade present in silvopasture systems could reduce heat stress associated with microclimatic conditions that characterize warm-weather portions of the year on the Coastal Plain of the Southeast USA. Objectives of this research were to:(1) quantify diurnal distribution patterns of landscape use and behavior of cattle in loblolly-pine (Pinus taeda) silvopasture versus open-pasture landscapes, and (2) relate observed differences in landscape use and cattle behavior patterns between the two pastures to differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 15 publications
1
32
0
1
Order By: Relevance
“…Hence, the null hypothesis is rejected. Lower dew point, relative humidity, wind speed, gust speed, total solar radiation, and PAR in silvopasture compared to openpasture are in agreement with previous findings in more mature tree stands (Karki and Goodman 2010;Rawat et al 1993;Valigura and Messina 1994). However, unlike previous findings with mature pine silvopasture or other forms of woodland, air temperature and soil temperature at 5 and 10 cm were higher in silvopasture compared to open-pasture in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, the null hypothesis is rejected. Lower dew point, relative humidity, wind speed, gust speed, total solar radiation, and PAR in silvopasture compared to openpasture are in agreement with previous findings in more mature tree stands (Karki and Goodman 2010;Rawat et al 1993;Valigura and Messina 1994). However, unlike previous findings with mature pine silvopasture or other forms of woodland, air temperature and soil temperature at 5 and 10 cm were higher in silvopasture compared to open-pasture in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The major changes in microclimatic conditions associated with tree development occur through creation of shade with interception of solar radiation and lowered wind speed as trees mature to form a physical barrier. Karki and Goodman (2010) found lower diurnal dew point (1-29 %), wind speed (29-58 %), gust speed (23-58 %), solar radiation (14-58 %), and photosynthetically active radiation (PAR) (10-72 %) from data collected for one day each in March, June, and September in a 20-year-old loblolly-pine (P. taeda L.)-bahiagrass silvopasture compared to an open-pasture landscape in Chipley, Florida, USA. With few exceptions, air temperature, soil temperature at 5 and 10 cm, and relative humidity were also lower in mature silvopasture compared to open-pasture.…”
Section: Introductionmentioning
confidence: 99%
“…During the early part of the dry season, almost the entire area in the intensive-shade system was shaded; therefore, the rarely spent time in the sun. KARKI & GOODMAN (2010) reported that grazing was the dominant activity in silvopastoral systems, while idleness was the major behavior in open pastures. These behavioral differences occurred mainly because of consistent variation in microclimatic conditions between systems.…”
Section: Visits To the Shaded Areasmentioning
confidence: 99%
“…Existing evidence on animal welfare comes mainly from the silvopasture literature and is inferred from grazing behavior and productivity gains. In silvopasture, animal welfare may be improved through less exposure to stressful microclimatic conditions and less time spent grazing (Karki and Goodman, 2010;Paciullo et al, 2008). Additional knowledge gaps include the survival of pathogens in animal manure in ICLS systems and subsequent infection or transmission to other individuals within the herd or potential implications for food safety.…”
Section: What Don't We Know?mentioning
confidence: 99%